Does memory improve with age? CD85j (ILT-2/LIR-1) expression on CD8 T cells correlates with 'memory inflation' in human cytomegalovirus infection. - Northfield, J; Lucas, M; Jones, H; Young, N; Klenerman, P (2005)
CMV-specific memory CD8(+) T cells accumulate over time to reach high frequencies amongst peripheral blood lymphocytes - a phenomenon termed 'memory inflation'. Using tetramer staining on samples from a large number of subjects and multivariate regression analysis, we were able to relate this to the phenotype of CD8(+) T cells. We made the following observations: (i) CD85j (ILT-2/LIR-1) was highly expressed alongside CD57 - an established effector memory marker - on CMV-specific CD8(+) T cells; (ii) on CD8(+) T cells as a whole, with increasing age, CD57 and CD85j (ILT-2/LIR-1) expression increased whereas CCR7 expression decreased, indicating increasing maturation of the total CD8(+) T-cell compartment with age; (iii) unit increases in the percentage of CMV-specific CD8(+) T cells expressing CD57 and CD85j (ILT-2/LIR-1) were associated with incremental expansion of these T-cell populations; (iv) CMV seropositivity is associated with a marked effect on the overall phenotype of CD8(+) T cells (at any given age, CMV seropositivity is associated with an 18.7% increase in CD85j (ILT-2/LIR-1) expression); and (v) from our observations we estimated from this an apparent 'ageing effect' of CMV on CD8(+) T cells of 35.4 years. The data presented are consistent with a predictable, unidirectional and linear model of virus specific T-cell differentiation and maturation.